"Light" in Malay Songket. Is it real? / Safial Aqbar Zakaria and Azizi Bahauddin - Zakaria, Safial Aqbar; Bahauddin, Azizi (Division of Research and Industry Linkages, UiTM Melaka, 2014)
This paper focus on the in depth meaning and philosophy of light of the songket motifs together with their traditions and historical associations. The motifs of songket, function as vehicles that bring together human minds to be aware of the relationship between the divine and spiritual realms with the physical world. This paper is an exploration of the motifs of songket, which can be seen as the "light" that symbolically represents the Supreme Creator of man, beast and nature. It is equally important to the function of light as a physical entity. The results of this research are mainly qualitative in nature. There are supported by structured interviews, personal observation, visual data to scrutinize the problems and questions raised in this research. The results have shown that the Malay has translated this appreciation of God's (Allah) beautiful creations into songket through the sense of the weaver, who then transmits these message to his mind and heart. This paper shows its relationship with the Malay, who created the cultural art and heritage by adding "soul" in their design, taldng the aspects of culture, belief and divinity, all of which open our minds to existence and relates it with light, in appreciating humanity and society.